Baxterianism: A Lexical History, 1650−1830 - Keeble, N. H. (The journal of ecclesiastical history, 2026)
The Oxford English dictionary’s earliest citation for the coinages Baxterianism and Baxterian to refer to the distinctive ecclesiological and theological thought of the seventeenth-century Puritan divine Richard Baxter is dated 1835, with no examples of use after 1839. This is incorrect. These, and related terms, originated in the 1650s and were in regular use during the intervening 185 years (as well as thereafter to the present day). This essay traces the changing signification and usage of these terms from the religious controversies of the seventeenth-century through the development of denominational identities and of a moderate tradition within eighteenth-century dissent that contributed to the development of Unitarianism.